2010
DOI: 10.1007/s00426-010-0290-7
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of structure-mapping inference by event-file binding and action planning: a model of tool-improvisation analogies

Abstract: Structure-mapping inferences are generally regarded as dependent upon relational concepts that are understood and expressible in language by subjects capable of analogical reasoning. However, tool-improvisation inferences are executed by members of a variety of non-human primate and other species. Tool improvisation requires correctly inferring the motion and force-transfer affordances of an object; hence tool improvisation requires structure mapping driven by relational properties. Observational and experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 98 publications
0
12
0
Order By: Relevance
“…Hyper-systemizers would be expected to perform better than "balanced" or mentalizer controls of matched verbal ability on semantic-association tests as employed in insight studies (Jung-Beeman et al, 2004;Kounios et al, 2007;Sandkuhler and Bhattacharya, 2008) and on standard verbal analogies (Gentner, 2003;Holyoak, 2005). Hyper-systemizers would also be expected to perform better than balanced or mentalizer controls of matched visuo-spatial ability on toolimprovisation problems, which are effectively visuo-spatial analogies (Fields, 2010). Conversely, hyper-mentalizers would be expected to perform no better than balanced or systemizer controls on mentalizing tasks, such as correctly inferring the intentions of actors in stories.…”
Section: Predictions Of the Default-network Deactivation Model Of Hypmentioning
confidence: 99%
“…Hyper-systemizers would be expected to perform better than "balanced" or mentalizer controls of matched verbal ability on semantic-association tests as employed in insight studies (Jung-Beeman et al, 2004;Kounios et al, 2007;Sandkuhler and Bhattacharya, 2008) and on standard verbal analogies (Gentner, 2003;Holyoak, 2005). Hyper-systemizers would also be expected to perform better than balanced or mentalizer controls of matched visuo-spatial ability on toolimprovisation problems, which are effectively visuo-spatial analogies (Fields, 2010). Conversely, hyper-mentalizers would be expected to perform no better than balanced or systemizer controls on mentalizing tasks, such as correctly inferring the intentions of actors in stories.…”
Section: Predictions Of the Default-network Deactivation Model Of Hypmentioning
confidence: 99%
“…Both this analogy and the others that appear explicitly in Rutherford (1911) are surprisingly similar to tool-improvisation analogies. It is shown here that these latter analogies can be implemented using the representational and inferential apparatus provided by the ''eventfile manipulation'' (EFM) model developed in Fields (2011a). Based on these EFM model implementations, it is suggested that electrons:nucleus::planets:sun is derivative from alpha-particle:central-charge::electron:atom, and that it is compelling not because it rests on the manipulation of concepts such as REVOLVE-AROUND, but because it rests on an ancient and ubiquitous motor memory of orbital motion.…”
Section: Introductionmentioning
confidence: 99%
“…In the almost three decades since the introduction of structure mapping as a formal model of analogy by Gentner (1983), a ''standard view'' of structure-mapping inference as mechanistically dependent on the recognition of explicit lexical symbols representing relational concepts, and hence as a humanspecific inferential capability, has come to dominate the analogy research community. This standard view has, however, recently been challenged by the observation that tool-improvisation analogies, which are carried out in the wild by many non-human animals, involve structuremapping inferences over force-motion relations (Fields 2011a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations